(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2008)
Several dinosaur footprints were discovered on three different levels cropping out in the CO.L.MAR quarry, south of the village of Borgo Celano in the Gargano Promontory (Apulia, southern Italy). The track-bearing levels belong to a carbonate inner platform succession referred to the Lower Cretaceous (upper Hauterivian-lower Barremian). This paper describes only the lowest dinoturbated bed, where footprints are preserved as natural cast. Forty footprints, mostly tridactyl, have been attributed to medium-sized theropods. Tridactyl tracks are similar to Kayentapus Welles, 1971 regarding ichnotaxonomy. Round shaped footprints, previously not described from this site, are found in association with tridactyl footprints and are related to ornitischian dinosaurs.